Assessing the Relevance of Montessori Education in Contemporary Contexts Using Bibliometric Analysis - Anisaturrizqi , Rita; Crismono, Prima Cristi; Yanuardianto, Elga (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2025)
The Montessori method remains a significant focus in early childhood education due to its emphasis on independence, exploration, and sensory-based learning. This study aims to map global academic trends on Montessori research from 2016 to 2024 using a bibliometric approach. Data were retrieved from the Scopus database using keywords such as “Montessori education,” “early childhood,” and “alternative learning models.” Analysis was conducted using VOSviewer, R (Bibliometrix), and Microsoft Excel to examine citation patterns, keyword associations, and geographical publication distributions. The results reveal fluctuating citation trends, with a peak in 2020 and a notable decline by 2024. Keyword mapping shows strong associations between Montessori and early childhood education, with emerging links to educational technology (EdTech). The United States leads in research output and academic influence, followed by Australia and Italy. This study introduces a new perspective by exploring the intersection between Montessori education and EdTech an area still underrepresented in early childhood research. The findings contribute conceptually by emphasizing how digital integration could sustain and innovate Montessori pedagogy. Overall, the study highlights the relevance of Montessori in contemporary education and encourages cross-disciplinary collaboration to explore its evolution in the digital era.